TINGKAT VISUALITAS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN GAYA BELAJAR - Farihah, Umi (Inovasi: Jurnal Diklat Keagamaan, 2016)
The purposes of this study is to analyze the students’ degree of visual insolving mathematics problems based on their learning style. This studyused descriptive and qualitative approach. The subjects of this study weresix students in the 8th grade at MTsN Kampak Trenggalek, on academicyear 2014-2015 with different learning style, two visual students, twoauditory students, and two kinesthetic students. Suwarsono’s (1982)Mathematical Processi ng Instrument (MPI ) was admi nistered todetermine their degree of visual. Based on the finding, it could beconcluded that the students’ degree of visual with visual learning style arevisual, the students’ degree of visual with auditory learning style areharmonic thinkers, and the students’ degree of visual with kinestheticare both visual and harmonic thinker.